East Asia by the year 2000 and Beyond : - Pape, Wolfgang (St. Martin's Press, 1998)
The Asia-Pacific Economic Cooperation (APEC) was founded in 1989. Since then the forum has developed into a major player in tri-partite relations between North America, East Asia and Europe. The Seattle and Bogor Summits were landmark events suggesting to many observers a gravitational shift in the world economy and world politics. Yet the Asian financial crisis had a sobering effect on high-flying expectations as APEC contributed little to crisis management. In the light of such contradictory performance, distinguished scholars here examine APEC's achievements and failures, its role and functions in international relations, its linkages with regional organisations and the interplay between the forum and national interests of major factors in the region.